Qualitative and Mixed-Methods Research in Translator Education: An Approach to Students Experiences and Perceptions - Singer-Contreras, N (UNIV FEDERAL SANTA CATARINA, NUCLEO TRADUCAO, 2022)
This paper presents two studies that focus on translation stu-dents perceptions at undergraduate level at a Spanish and two Chilean universities. Both studies aim to improve translation education. The first study analysed the students self-efficacy beliefs at the undergraduate de-gree in Translation and Interpreting offered at the University of Granada. To do this, a quasi-experimental field design and a mixed-methods appro-ach was employed to study the development of the students self-efficacy beliefs and to discover and analyse their perceptions of a) the teaching practices that influenced their self-efficacy beliefs during their education as translators, and b) the reasons why this influence occurred (or not). In the second study, the students perceptions were explored using a qualita-tive method, namely the Interpretative Phenomenological Analysis (IPA), which fostered the understanding of the development of translator iden-tity of students at the Translation Studies undergraduate programmes at Universidad de Santiago de Chile and Pontificia Universidad Catolica de Valparaiso. This paper describes both approaches and highlights the re-levance of employing approaches with a strong qualitative component to gain access to the psychology of translation students. In other words, these approaches go beyond most quantitative approaches which have traditio-nally been used to study these perceptions.